Therapy Efficacy of Idiopathic Ventricular Extrasystoles: A Real Life Study - Aliisa Lönnrot; Jaakko Inkovaara; Olli Arola; Tero Penttilä; Heikki Mäkynen; Katriina Aalto-Setälä; Sinikka Yli-Mäyry (Journal of Interventional Cardiology)
Background. Ventricular extrasystoles (VESs) are common and often harmless in a healthy heart, but they can significantly affect the quality of life. If changes in lifestyle and antiarrhythmic medication are not enough, invasive and often curative catheter ablation can be considered. Better understanding of the conformation of VESs with a 12-lead ECG, as well as their precise localization, have increased their treatment with catheter ablation. Our goal was to determine whether the anatomical site of VES had an effect on procedure success. We also analyzed the safety of the procedure and patient-related factors affecting the results. Materials and Methods. In this retrospective study, we analyzed the medical records of 63 consecutive patients with multiple idiopathic VESs treated by catheter ablation at Heart Hospital, Tampere University Hospital, during 2017 and 2018. Patients with structural heart disease were excluded. Ablation success was estimated with two endpoints, primary and follow-up success. Results. The majority of the patients received treatment on the right ventricular outflow tract (66.7%), others on the left ventricle (17.5%), or the aortic cusp (9.5%). The site of origin remained unknown in four procedures (6.3% of patients). Primary success was observed in 48 procedures (76.2%). During the follow-up period of three months, the procedure was successful in 70.3% of the cases. The anatomical site of VES had no significant effect on either primary or follow-up success. Those with a successful follow-up result had a lower body mass index (BMI = 26.4) than those who had an unsuccessful result (BMI = 28.7; p=0.069); this did not reach statistical significance, potentially due to the small study population size. Complications were observed in three patients (4.5%). All of them were related to the catheter insertion site. Conclusions. For a symptomatic patient, catheter ablation is an effective and often fully curative treatment. The success rate was similar regardless of the site of VESs. This suggests that catheter ablation should also be assessed early on for other cases besides classic right ventricular outflow tract VESs. A high BMI was the only factor associated with a poor procedure success rate. The procedure itself is safe, and adverse effects are rare. The radiation dose is also low partly due to the current magnetic navigation method.